2017
DOI: 10.2355/isijinternational.isijint-2017-125
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-situ</i> Observation of <i>δ</i>↔<i>γ</i> Phase Transformations in Duplex Stainless Steel Containing Different Nitrogen Contents

Abstract: The characteristics of the γ ↔δ phase transformations were observed on the surface of duplex stainless steels with different nitrogen concentrations by the Ultra High Temperature Confocal Laser Scanning Microscope (UHT-CSLM). The effects of the nitrogen content on the phase transformations are discussed based on the experimental results and thermodynamic calculations. It is found that the migration of the δ/γ IB is the main form of the phase transformation and leads to the continuous decline and final disappea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…At the early stage of the growth of the δ-ferrite platelet, the migration rate of the δ/γ IBs is mainly controlled by δ/γ IB types due to the short-range diffusions of all elements that occur near the thin δ/γ IBs. δ/γ IBs at the tip of δ-ferrite platelets are incoherent with high mobility, although the δ/γ IBs along the thickness direction are semi-coherent with low mobility [26,27]. As a result, the migration rate of the δ/γ IBs along the longitudinal direction is far greater than along the transverse direction.…”
Section: Discussionmentioning
confidence: 99%
“…At the early stage of the growth of the δ-ferrite platelet, the migration rate of the δ/γ IBs is mainly controlled by δ/γ IB types due to the short-range diffusions of all elements that occur near the thin δ/γ IBs. δ/γ IBs at the tip of δ-ferrite platelets are incoherent with high mobility, although the δ/γ IBs along the thickness direction are semi-coherent with low mobility [26,27]. As a result, the migration rate of the δ/γ IBs along the longitudinal direction is far greater than along the transverse direction.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, more attention was paid to the solid-state phase transition of δ-phase in the steels, and the formation of the δ-phase in the solidification stage was less studied [10,11]. Generally, the process of the δ-phase formation in the F/M steel is more complicated than that in the austenitic heat-resistant steel.…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature confocal microscopy (HTCM) was used to observe the solidification process of S32101 DSS in the present research, and this technique can provide a so-called in situ observation. Zhao and Sun [ 4 ] applied laser scanning confocal microscopy (LSCM) in their research on DSS. They observed and discussed the effect of different N contents on the solid-state δ γ phase transformations and concluded that N could hinder the migration of δ/γ interface boundaries (IBs).…”
Section: Introductionmentioning
confidence: 99%